Student Career Readiness from an Industrial Guidance and Counseling Perspective in Higher Education - Dina Nuriani; Nor Syifahayati; Vidya Nur Farida; Delvia Rahmawati; Ahmad Rhicho Widianto; Karyanti Karyanti; Asep Solikin (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: The dynamic development of the industrial world requires higher education students to possess adaptive, sustainable career-readiness. Aim: This study aims to describe students' career readiness from the perspective of Industrial Guidance and Counseling and to examine its distribution across respondents' characteristics. Method: The study employed a quantitative, descriptive design. The research subjects consisted of 204 students from the Faculty of Teacher Training and Education. Data were collected using a structured instrument and analyzed using descriptive statistics, including frequencies and percentages. Results and Discussion: The results indicate that the majority of students fall into the moderate and high categories of career readiness, with a very small proportion in the low category. Distribution by gender shows a relatively balanced pattern, suggesting that differences in career readiness are not significantly influenced by gender. These findings suggest that students already possess basic readiness to enter the workforce; however, further strengthening is still needed in aspects of adaptability and career planning. Conclusion: The study concludes by emphasizing the important role of Industrial Guidance and Counseling in optimizing students' career readiness. Recommendations are directed toward developing structured career counseling services and to further research employing more comprehensive variables and research designs.